2019
DOI: 10.22146/mgi.38813
|View full text |Cite
|
Sign up to set email alerts
|

Pendugaan Distribusi Air Lindi dengan Geolistrik Metode ERT di TPA Piyungan, Bantul, DIY

Abstract: TPA Piyungan menampung sampah hingga 550 ton/hari, sehingga air lindi (leachate) yang dihasilkan akan lebih besar dan dapat berdampak pada airtanah. Tujuan dari penelitian ini adalah untuk mengidentifikasi pencemaran air lindi pada airtanah di sekitar TPA Piyungan, dan dilakukan dengan menggunakan metode Electrical Resistivity Tomography (ERT) konfigurasi Wenner Beta, flownet, dan uji sifat fisik-kimia air. Hasil dari penelitian adalah (1) aliran airtanah secara dominan bergerak ke arah Barat Laut dari TPA Piy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
3
0
2
Order By: Relevance
“…Another study that supports the estimation of the resistivity value of peat soil is Fajania et al (2021), which states that the resistivity value of peat soil is in the range of 18.8-126 Ωm (Fajania et al, 2021). Ramadhaningsih and Sampurno's research (2017) also states that the resistivity interpretation value on peat ranges from 17.6-69.9 Ωm (Ramadhaningsih and Sampurno, 2017). The depth of peat soil in Batu Layang landfill was estimated to be up to 4.5 m below the soil surface (Muhardi et al, 2020).…”
Section: Analysis Of the Distribution Of Leachate Below The Soil Surf...mentioning
confidence: 85%
See 1 more Smart Citation
“…Another study that supports the estimation of the resistivity value of peat soil is Fajania et al (2021), which states that the resistivity value of peat soil is in the range of 18.8-126 Ωm (Fajania et al, 2021). Ramadhaningsih and Sampurno's research (2017) also states that the resistivity interpretation value on peat ranges from 17.6-69.9 Ωm (Ramadhaningsih and Sampurno, 2017). The depth of peat soil in Batu Layang landfill was estimated to be up to 4.5 m below the soil surface (Muhardi et al, 2020).…”
Section: Analysis Of the Distribution Of Leachate Below The Soil Surf...mentioning
confidence: 85%
“…The advantages of this geoelectric method are that it does not pollute the environment, easy and fast operation, lower costs compared to using other geophysical methods, and identifies depths up to several 50 feet below the ground surface (Miswar, 2017). Many studies have used the geoelectric method to study the distribution of leachate below the soil surface, including the Estimation of Leachate Distribution with the Geoelectrical ERT Method (Ramadhan et al, 2019); Application of the Wenner mapping configuration geoelectric method to determine leachate seepage at Talang Gulo Jambi landfill (Pratiwi et al, 2018) and Identification of the direction of leachate seepage using the resistivity geoelectric method of dipole-dipole configuration around the Sekoto landfill, Kediri district (Ratih et al, 2021). Therefore, the geoelectrical method is needed to indicate the leachate distribution below the soil surface.…”
Section: Introductionmentioning
confidence: 99%
“…So, it was known that the West-Northwest area tends to have a lower groundwater level than the landfill area. The groundwater flows towards the West-Northwest (Figure 1) also showed that the area tends to have shallow groundwater levels (Ramadhan et al, 2019).…”
Section: Regional Hydrogeologymentioning
confidence: 95%
“…Pada sumur 1 dan sumur 2 nilai TDS sudah memenuhi baku mutu, namun pada sumur 3, nilai TDS melebihi baku mutu. Hal ini dapat terjadi karena sumur 3 jaraknya paling dekat dengan TPA Regional Piyungan, dimana terjadi proses pencucian polutan sampah menjadi air lindi, sehingga menyebabkan kualitas air tanah menurun (Ramadhan et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…Nitrat (NO 3-) merupakan ion yang terdapat dalam perairan dengan jumlah sedikit (Ramadhan et al, 2019). Parameter nitrat pada air sumur masyarakat bulan April 2023 adalah 2 mg/L, 11 mg/L, dan 37 mg/L.…”
Section: Hasil Dan Pembahasanunclassified